2019
DOI: 10.1590/1982-0216/20192156119
|View full text |Cite
|
Sign up to set email alerts
|

Association between auditory temporal and visual processing in reading skill

Abstract: Purpose: to verify whether students screened with altered auditory temporal processing are more likely to present altered visual processing. Methods: the sample consisted of 68 children, aged from 9 to 12 years, 53% males, from the 5th and 6th grades of a public school. All children with alterations in the audiological or ophthalmological evaluation were excluded. The Duration Pattern Test (screening for auditory temporal skill), the Reading Perceptual Scale (visual stress symptom questionnaire and colored ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
3
0
4
Order By: Relevance
“…O estresse visual não é uma doença, mas sim um distúrbio do processamento visual que ocorre como resultado de um déficit no sistema magnocelular visual (Garcia et al, 2019;Stein & Walsh, 1997;Vilhena, Guimarães, Guimarães, Pinheiro, 2021a). A nomenclatura 'síndrome de Irlen' é comumente utilizada na área da Educação no Brasil.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O estresse visual não é uma doença, mas sim um distúrbio do processamento visual que ocorre como resultado de um déficit no sistema magnocelular visual (Garcia et al, 2019;Stein & Walsh, 1997;Vilhena, Guimarães, Guimarães, Pinheiro, 2021a). A nomenclatura 'síndrome de Irlen' é comumente utilizada na área da Educação no Brasil.…”
Section: Discussionunclassified
“…A década de 2010 no Brasil foi marcada pelos primeiros estudos do LAPAN-UFMG, como demonstrado na revisão de Vilhena et al (2020). Tem-se como exemplo os estudos de Garcia et al (2017Garcia et al ( , 2019, que investigaram o estresse visual em uma amostra populacional de alunos (n = 68, 9 a 12 anos, 53% meninos) do 5º e 6º ano do Ensino Fundamental, em São Paulo, Brasil. Garcia et al verificaram que 13% dos participantes, com o uso das Irlen Overlays, apresentaram ganhos de pelo menos ≥15% na taxa de leitura.…”
Section: Discussionunclassified
“…The articles were organized in chronological order of publication, along with the summary of results focusing on the effects of the overlays (Table 1). Concerning language, all articles (n = 12) had been published in English, with one with a version in Portuguese as well 15 . As for the country of origin, the study reported in these articles were mainly conducted in England (n = 8), followed by Brazil (n = 3) and Scotland (n = 1).…”
Section: Methodsmentioning
confidence: 99%
“…A velocidade de processamento com que a informação é acessada vai depender da capacidade de identificar estímulos de forma rápida e sucessiva, que tende a se intensificar com a precisão do acesso ao léxico pré-existente. A recuperação de aspectos sensoriais pelas vias auditiva e visual, se fortalecem e se ramificam ao aprendizado da linguagem, possibilitando a ampliação da memória e do acesso lexical (LAMBERT;SPINATH, 2018;GARCIA et al, 2019).…”
Section: Introductionunclassified
“…As perspectivas de análise do processamento fonológico propostas na fonoaudiologia e pela psicologia cognitiva, fortalecem o pressuposto de identificação e intervenção cada vez mais precoce quanto aos aspectos relacionados a integralidade do processamento fonológico. O que amplia o leque de possibilidades interventivas precoces, integrando a consciência fonológica à memória operacional e ao acesso e composição lexical, enquanto medidas fundamentais que fortalecem a aprendizagem da leitura e escrita (ROSAL et al, 2016;WILLOUGHBY et al, 2017;GARCIA et al, 2019).…”
Section: Introductionunclassified